Socio-economic vulnerability and neo-liberalism: lessons from Bangladesh - Rahman, Shahidur (© 2009, Sage Publication, UK, 2019)
This article was published in the South Asia Research [© 2009, Sage Publication, UK] and the definite version is available at :https://doi.org/10.1177/026272800902900303. The Journal's website is at: https://journals.sagepub.com/doi/10.1177/026272800902900303